2023
DOI: 10.7759/cureus.37731
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expandable Metal Stent (SEMS) Versus Lumen-Apposing Metal Stent (LAMS) for Drainage of Pancreatic Fluid Collections: A Randomized Clinical Trial

Abstract: Background and aimEndoscopic ultrasound (EUS)-guided drainage is the gold standard approach for the treatment of encapsulated pancreatic collections (EPCs) including pseudocyst and walled-off pancreatic necrosis (WON), and is associated with an equivalent clinical efficacy to surgical drainage with fewer complications and less morbidity. Drainage may be achieved via several types of stents including a fully covered self-expandable metallic stent (SEMS) and lumen-apposing metal stent (LAMS). However, to date th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Additionally, Amato et al ( 28 ) demonstrated that a longer removal time did not increase the risk of AEs. Recent randomized controlled trials (RCTs) have not shown the superiority of LAMS over DPPS or an increased bleeding risk for WON ( 29 31 ), nor have they demonstrated superiority of LAMS over SEMS for PFCs ( 32 ).…”
Section: Endoscopic Ultrasound-guided Drainage Of Pancreatic Fluid Co...mentioning
confidence: 99%
“…Additionally, Amato et al ( 28 ) demonstrated that a longer removal time did not increase the risk of AEs. Recent randomized controlled trials (RCTs) have not shown the superiority of LAMS over DPPS or an increased bleeding risk for WON ( 29 31 ), nor have they demonstrated superiority of LAMS over SEMS for PFCs ( 32 ).…”
Section: Endoscopic Ultrasound-guided Drainage Of Pancreatic Fluid Co...mentioning
confidence: 99%